Preparation and evaluation of sweet potato starch-blended sodium alginate microbeads - Jha, Antesh K; Bhattacharya, A (Asian Journal of Pharmaceutics (AJP), 2014)
The design of effective drug delivery systems has recently become an integral part of the development of new medicines. Hence, research continuously keeps searching for ways to deliver drugs over an extended period of time with a well- ontrolled release profile.The ionotropic gelation method was used to prepare sweet potato starch-blended controlledc release alginate microbeads of ibuprofen. Sweet potato is an important crop in many developing countries. Although sweet potato originated from Central America, its ability to adapt to a wide variety of climatic conditions allows it to grow both in tropical and in moderate temperature regions of Africa, Asia and the Americas. The influence of various formulation factors such as in vitro drug release, entrapment efficiency, swelling study and micrometric properties was investigated. Other variables included sweet potato starch concentration, percentage drug loading, curing time, cross-linking agent and stirring speed during the microencapsulation process. The entrapment efficiencies were found in the range of 71.85 ± 2.04 - 94.53 ± 1.02%. The particle sizes were found in the range of 0.82 ± 0.006 - 1.08 ± 0.009 mm. This suggested that the ionotropic gelation method was successful in producing sweet potato starch-blended alginate microbeads.